2005
DOI: 10.1227/01.neu.0000148899.39020.87
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Intraoperative Diagnoses Using Smear Preparations from Stereotactic Brain Biopsies: Intraoperative versus Final Diagnosis—Influence of Clinical Factors

Abstract: Intraoperative diagnosis with stereotactic biopsy has high validity. Immediate treatment based on the intraoperative diagnosis can be justified (e.g., for metastases or glioblastomas). Stereotactic biopsy with an exact histopathological diagnosis is strongly recommended for planning adequate therapy for patients with unidentified brain lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
88
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 26 publications
7
88
1
1
Order By: Relevance
“…Tilgner et al found almost 90% complete correlation for the group of primary and secondary lymphomas in their study to validate intraoperative diagnoses using smear preparation from stereotactic brain biopsies (Tilgner et al, 2005). However we have encountered certain diagnostic pitfalls in our experience.…”
Section: Discussionmentioning
confidence: 93%
“…Tilgner et al found almost 90% complete correlation for the group of primary and secondary lymphomas in their study to validate intraoperative diagnoses using smear preparation from stereotactic brain biopsies (Tilgner et al, 2005). However we have encountered certain diagnostic pitfalls in our experience.…”
Section: Discussionmentioning
confidence: 93%
“…
Specialists institute a variety of diagnostic audits to identify areas of weakness and to optimize clinical performance [1][2][3][4][5] . In pathology, one common diagnostic event well-suited to this type of analysis is the intraoperative consultation where touch, smear and frozen section preparations have long been used to assist surgical decision making [6][7][8][9] .

Neurosurgeons incorporate a neuropathologist's interpretation into the surgical plan through intraoperative consultations on small biopsies 5,6,8,10 .

…”
mentioning
confidence: 99%
“…In pathology, one common diagnostic event well-suited to this type of analysis is the intraoperative consultation where touch, smear and frozen section preparations have long been used to assist surgical decision making [6][7][8][9] .Neurosurgeons incorporate a neuropathologist's interpretation into the surgical plan through intraoperative consultations on small biopsies 5,6,8,10 . These consultations represent a diagnostic challenge for the neuropathologist that imposes sampling and technical limitations under a relative time constraint.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nondiagnostic tissue samples occurred at a rate of 4.6%-5%. 10,30 In the current practice setting, there is a high degree of subjectivity in the management of patients with cerebral metastasis who have radiographic and/or clinical progression after SRS. While our study is limited by the small sample size, it represents a systematic effort to address a clinically important question.…”
Section: Discussionmentioning
confidence: 99%